1952
DOI: 10.1172/jci102646
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Choline Absorption in the Intestinal Tract 1

Abstract: Previous investigations ( 1 ) have demonstrated that in normal persons approximately 60 per cent of choline salts fed in a single dose is transformed by intestinal bacteria to trimethylamine (TMA), which is excreted in the urine mainly as the oxide. In chronic liver diseases, considerably less of the ingested choline appears in the urine as total trimethylamines (TTMA). This difference was considered as evidence of an altered action of the intestinal bacteria in these diseases ( 1 ). The concept of the intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1953
1953
2000
2000

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 3 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…Serum albumin and globulin were determined by Weichselbaum's (1946) method as modified by Wolfson et al (1948). Thymol turbidity was estimated by Maclagan's (1944) method as modified by De la Huerga and Popper (1949), zinc sulphate turbidity according to Kunkel (1947), serum urea by the method of Archer and Robb (Harrison, 1947), and serum urate by the spectrophotometric method of Praetorius and Poulsen (1953).…”
Section: Serum Chemistrymentioning
confidence: 99%
“…Serum albumin and globulin were determined by Weichselbaum's (1946) method as modified by Wolfson et al (1948). Thymol turbidity was estimated by Maclagan's (1944) method as modified by De la Huerga and Popper (1949), zinc sulphate turbidity according to Kunkel (1947), serum urea by the method of Archer and Robb (Harrison, 1947), and serum urate by the spectrophotometric method of Praetorius and Poulsen (1953).…”
Section: Serum Chemistrymentioning
confidence: 99%
“…Choline was given orally in the form of bicarbonate 1 in amounts containing 4 Gm. choline base (460 mg. N) with the exception of the four normal subjects who received 5.4 Gm.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the evidence gathered to establish this phenomenon was that, following ingestion of choline with aureomycin, much less TTMA than usual were excreted (3,4). Further experiments were undertaken to elaborate upon the inhibition of TTMA formation from choline by antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…De la Huerga and Popper (1,2) conclude that most of the ingested choline in man is converted to trimethylamine (TMA) or its oxide (TMAO), through the action of bacteria in the small intestine and that these products are then absorbed. Wiinsche (3) (6) show that liver homogenate and liver slices are able to convert choline to TMA.…”
mentioning
confidence: 99%
“…Harris (1) found that all available pyridoxineless mutants of Neurospora sitophila grow better a t limiting pyridoxine concentrations if thiamine…”
mentioning
confidence: 99%